PENGARUH KUALITAS PRODUK, KUALITAS PELAYANAN, DAN CITRA TOKO TERHADAP KEPUASAN KONSUMEN TOKO RITEL - Ahmadi; Muhyidin, Ahmad (ESA : JURNAL KAJIAN EKONOMI SYARIAH, 2022)
Looking at it from a business phenomenon above, the researcher intends to conduct research with the title: "The Effect of Product Quality, Service Quality, and Customer Satisfaction Against Image Store Retail Stores". The population in this study is the wholesaler who became Amin Jaya consumers shop Jepara regency. Sample of 100 respondents was taken and the techniques used are nonprobability sampling technique with purposive sampling approach. Data was collected using a survey method through questionnaires filled out by consumers. Then the data were analyzed by using regression analysis. This analysis includes the Test Validity, Reliability Test, regression analysis, and hypothesis testing through f and t test. From the analysis using linear regression can be seen that the variable product quality, service quality and store image has a positive effect on customer satisfaction Amin Jaya store. The analysis using the t test can know the quality of service and the image of the store has a positive effect on customer satisfaction and the quality of the product does not affect the consumer satisfaction. The analysis using the coefficient of determination is known that 40.5% customer satisfaction variables can be explained by the variation of the variable product quality, service quality and store image. While the rest is explained by other variables.